2019
DOI: 10.2135/cropsci2019.05.0304
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the C Genome of Different Variants of Brassica oleracea for the Improvement of Agronomic and Seed Quality Traits of B. napus Canola

Abstract: The narrow genetic base of Brassica napus L. canola, especially of its C genome, is an impediment for continued improvement of this crop. We investigated the gene pools of different variants of B. oleracea L. to improve agronomic and seed quality traits of B. napus canola. For this, B. napus canola inbred populations were developed from six interspecific crosses, involving a single B. napus canola line and six accessions of B. oleracea belonging to four variants of this species, following two breeding techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Of the six population studied, the inbred population derived from the cross involving broccoli gave higher yield than the inbred populations derived from the other five crosses. While evaluating only the inbred lines in larger plot (5.0 m × 1.7-1.8 m) trials, we also found similar results (Nikzad et al, 2019). However, in this study, we found that the test hybrids of the inbred population of broccoli yielded less than the other test hybrid populations; this inbred population, in fact, had the least genetic distance from the B. napus parent (data not shown).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Of the six population studied, the inbred population derived from the cross involving broccoli gave higher yield than the inbred populations derived from the other five crosses. While evaluating only the inbred lines in larger plot (5.0 m × 1.7-1.8 m) trials, we also found similar results (Nikzad et al, 2019). However, in this study, we found that the test hybrids of the inbred population of broccoli yielded less than the other test hybrid populations; this inbred population, in fact, had the least genetic distance from the B. napus parent (data not shown).…”
Section: Discussionsupporting
confidence: 79%
“…Genomic DNA of the above-mentioned 227 (110 + 117) F 2 -and BC 1 -derived inbred lines and their seven parents (B. napus A04-73NA and six B. oleracea cultivars/lines) was extracted using SIGMA DNA extraction kit (Sigma-Aldrich, St. Louis, MO, USA) following manufacture's instruction. A total of 95 polymorphic SSR markers (Nikzad et al, 2019) from nine Cgenome linkage groups (LG) were selected from 418 markers for genotyping the populations. Polymerase chain reactions (PCR) for amplification of the genomic DNA was performed in a total volume of 15.5 μl, which included 20 ng genomic DNA, 5× PCR reaction buffer, 25 mM MgCl 2 , 0.6 unit Taq DNA polymerase (Promega Corporation, Madison, WI), 10 mM each dNTP (Invitrogene Life Technologies Inc., Burlington, ON), 5 μM of each forward and reverse primer, and 5 μM tag F (fluorescent dyes FAM, VIC, NED, and PET).…”
Section: Simple Sequence Repeat (Ssr) Marker Analysismentioning
confidence: 99%
“…A total of 184 B. napus inbred lines, which included 90 F 10 and 94 BC 1 F 9 lines, developed from F 2 and BC 1 (F 1 × B. napus parent) of six B. napus × B. oleracea interspecific crosses involving the single B. napus line and the six B. oleracea lines and cultivars were used in this study. The detail of the development of these B. napus inbred lines and confirmation of their euploid (2 n = 38) nature was described previously (Iftikhar et al., 2018; Nikzad et al., 2019). In brief, the F 1 plants of the six interspecific crosses were self‐pollinated for F 2 seeds and were also backcrossed to the B. napus parent for BC 1 seeds.…”
Section: Methodsmentioning
confidence: 99%
“…We developed an inbred B. napus population from six interspecific crosses of B. napus × B. oleracea (AACC × CC = F 1 ACC) involving different varieties of B. oleracea to broaden the genetic base of the C genome of B. napus canola (Iftikhar et al., 2018; Nikzad et al., 2019). Given that wide diversity exists in B. oleracea (e.g., Izzah et al., 2013; Thakur et al., 2018), this population was expected to be highly diverse for the C genome and carry alleles which are not present in natural B. napus .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in the process of teaching [6][7][8] . we should pay attention to the introduction of the overall framework of the discipline to help students learn and transfer; guide students to explore the scientific theory and practical knowledge of the subject; select key contents and elaborate on key contents; arrange homework after class to improve the ability of analysis and calculation; and finally, carry out practice to improve perceptual knowledge [9][10][11] .…”
Section: Figure 1 Basic Teaching Linksmentioning
confidence: 99%